Health risk factors and health promoting behaviour among medical and non-medical students - M., Norhaini; Hazali, Norazlanshah; M.I., Khairil Anuar; M.F., Fazlyla Nadya; M., Mashita; G.M., Mohamad (Malaysian Public Health Physicians’ Association, 2014)
Students in tertiary level education are mostly young adults that are transiting from the teenage years to adulthood. Since there is less restriction as compared to their teenage years, university and college students might involve in risky behaviours that may affect their health, social and academic performance. Thus, the purpose of this study is to investigate and identify the differences of health risk factors and health promoting behaviour that have been practiced by students in Malaysia. A cross sectional study was conducted using closed-ended questionnaires distributed to university and college students via emails. The results showed that 77.0% students claimed they have no health problem. However 49.0% of the non-medical students did not know whether they have normal BMI. Among the medical students, 62.0% rarely do physical exercise even though most are seriously concern about their fat consumption (95.0%). Only 30.0% of the total students have awareness of wearing seat belt. For health promoting behaviour, 33.0% of female students have never perform breast self examination (BSE), while 65.0% of male students have never perform testicular self examination (TSE). These findings confirmed that there are differences in health risk factors and health promoting behaviour that have been practiced by the students.